Association of intraoperative pulse pressure drop and minimum mean arterial pressure with postoperative length of stay: A stratified reanalysis of published data by age and sex - Victor Beaucoté; Jérôme Cartailler; Jérémie Mattern; Bernard Trillat; Etienne Gayat; Morgan Le Guen; Marc Fischler (PLoS ONE, 2026)
Objective Intraoperative hypotension (IOH) is associated with postoperative organ dysfunction, but no universal definition exists. Guidelines recommend a mean arterial pressure (MAP) threshold of 60–70 mmHg. Prolonged postoperative length of stay (pPOLOS) serves as a proxy for organ injury. This study explores the association between IOH and pPOLOS risk, accounting for patient characteristics (sex and age). Design Retrospective, single-center cohort study of adult patients undergoing general anesthesia for scheduled non-cardiac surgery between July 2017 and December 2019. Methods pPOLOS was defined as a LOS higher than the median value (main outcome). Relationships between pPOLOS risk and three previously identified IOH variables—drop in pulse pressure (DropPP: difference between maximum and minimum values), minimal MAP (MinMAP), and cumulative time with pulse pressure > 61 mmHg per hour of surgery (CumTimePP > 61 mmHg)—were modeled using piecewise linear splines. Results Our study examined 9,516 patients. For the whole population, the relationship between DropPP and pPOLOS risk was pseudolinear with no activation threshold (slope 0.29–0.52%/mmHg). For MinMAP, an activation threshold of 73 mmHg was identified, below which the association became linear (slope: −0.64%/mmHg). For CumTimePP > 61 mmHg, pPOLOS risk increased sharply (initial slope: 8.40%/min) and reached a saturation threshold at two minutes. Women demonstrated a lower pPOLOS risk and a lower IOH threshold than men. In contrast, older patients (≥65 years) exhibited a higher baseline pPOLOS risk and showed no identifiable IOH threshold. Conclusions The identified IOH threshold (MAP < 73 mmHg) is in line with values reported in the existing literature. Pulse pressure variability, age, and sex emerged as key determinants of pPOLOS risk.